National and Office‐Specific Measures of Auditor Industry Expertise and Effects on Audit Quality - REICHELT, KENNETH J.; WANG, DECHUN (Journal of Accounting Research, 2010)
ABSTRACT Our paper examines whether audit quality is higher for industry audit specialists at the national and city‐office levels using the framework developed in Ferguson et al. [2003] and Francis et al. [2005] . We find that auditors who are both national and city‐specific industry specialists have clients with the lowest abnormal accruals, suggesting that joint national and city‐specific industry specialists have the highest audit quality. In addition, we find some evidence that abnormal accruals of firms audited by city‐industry specialists alone (without also being national specific industry specialists) are lower than those audited by nonindustry specialists. Using alternative measures of audit quality, we find that when the auditor is both a national and a city‐specific industry specialist, its clients are less likely to meet or beat analysts' earnings forecasts by one penny per share and more likely to be issued a going‐concern audit opinion. Together these results provide consistent evidence that audit quality is higher when the auditor is both a national and city‐specific industry specialist, suggesting that auditors' national positive network synergies and the individual auditors' deep industry knowledge at the office level are jointly important factors in delivering higher audit quality.